(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2020)
In this paper I compare George Berkeley’s evaluation of utility of the Christian religion, as presented in his Alciphron (1732), with John Stuart Mill’s re-evaluation, contained in his posthumously printed essay Utility of Religion (1874). I obviously take also into account the two philosophers’ other works provided the utility in question is discussed there to some important extent. I argue, among others, that Berkeley’s claim that the Christian religion is necessarily and most greatly useful, i.e. inevitably leads to the happiness of mankind, as well as Mill’s acceptance of rather the contrary claim, logically depend on assumptions regarding either the world as such (Berkeley), or the human mind as such (Mill), hence one cannot, indeed, decide the problem apart from taking them into consideration.